PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD MENGGUNAKAN MEDIA GAMBAR PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR - Suci Handayani; Made Ayu Pransisca (STKIP Subang, 2025)
This study aims to describe the application of the cooperative learning model (STAD) with the aid of image media in thematic learning in elementary schools. The research method used in this study is quantitative. Based on the results, it can be seen from the average pretest score of 48.08 and posttest score of 78.3.